l-carnitine in critically ill patients—a case series study - Takehiko Oami (Renal Replacement Therapy, 2018)
Abstract Background l-carnitine is essential for lipid metabolism, and lack of l-carnitine intake and loss by treatments lead to carnitine depletion causing muscle weakness, anemia, and immune dysfunction. Carnitine depletion occurs in critically ill patients after long treatments, but its epidemiology or the risk factors remain unclear. This study aims to investigate the prevalence and risk factors of l-carnitine depletion in critically ill patients. Methods Sixty-four patients were enrolled for the study. Total and free l-carnitine concentrations (t- and f-Carnitine) were measured at ICU admission and every 7 days afterward during hospitalization. Acylcarnitine- to f-Carnitine ratio (A/F Carnitine ratio) was analyzed in a subgroup of patients treated with continuous renal replacement therapy (CRRT). Acylcarnitine concentration was calculated as the difference between t- and f-Carnitine concentrations. Results Carnitine deficiency (f-Carnitine < 36 nmol/mL) was observed in 15 (23.4%) patients at ICU admission. Low body mass index (BMI < 19.5) was associated with a subsequent reduction of l-carnitine during the ICU stay (AUC = 0.81, p < 0.01). Sequential Organ Failure Assessment (SOFA) score was correlated with l-carnitine reduction but without a significant cutoff value. Patients treated with CRRT demonstrated elevated A/F Carnitine ratio (p < 0.05), possibly due to insufficient elimination or impaired metabolism of carnitine. Conclusions Less than one fourth of critically ill patients had carnitine deficiency at ICU admission, while low BMI and high SOFA scores were identified as potential risk factors for reduction of l-carnitine. Patients treated with CRRT presented signs of impaired carnitine metabolism. Further studies to investigate the potential benefits of l-carnitine supplementation may be warranted in these patients. Trial registration UMIN000013352. Registered 6 March 2014.